Theoretical Study of Employment Issues - Ardiansyah Hamid; Kadek Wiwik Indrayanti; Diah Aju Wisnuwardhani (Jurnal Cakrawala Hukum, 2023)
The problem raised in this research is regulating workers' rights and their protection in the Law. This study uses normative legal research methods with several approaches, namely the statutory and conceptual approaches. The results of this study state that the rights of workers/laborers are essential to implement because if workers and laborers are not given rights that are by human rights, then the work carried out by workers will not be able to run correctly. Whereas the contents of the manpower articles in the Law still have several normative problems, namely not yet providing guarantees of legal certainty for guarantees for the protection of workers' rights, such as determining proper wages and eligibility for severance pay. Likewise, with the provisions regarding layoffs, the Law only accommodates the interests of employers so that it can have implications for unilateral termination of employment relations with workers. The philosophical concept of Law is still co-opted with the liberal economic spirit, which is the fundamental basis for the birth of the Law, resulting in most people's rejection of the Law.How to cite item: Hamid, Ardiansyah, Kadek Wiwik Indrayanti, and Diah Aju Wisnuwardhani. â€œThe Issue of Labor Law Versus Human Rights.â€ Jurnal Cakrawala Hukum 14 no. 1 (2023): 96-105. DOI: 10.26905/idjch.v14i1.9873.